TINDAK PIDANA MEMPRODUKSI KOSMETIKA TANPA IZIN PRODUKSI DAN TIDAK MEMENUHI STANDARD PERSYARATAN KEAMANAN - Budiyono, Wisnu Laksana; Djaja, Dudik; Subekti, Subekti; Ucuk S, Yoyok (Universitas Muhammadiyah Ponorogo, 2024)
Consumers who want to improve their appearance are often attracted to cheap cosmetics because they provide fast results. This is what makes them look for alternative ways by buying these products even though they may not meet the requirements and these cosmetics are sold freely but do not have a BPOM number. The aim of this research is to analyze liability in the production of cosmetics without a production permit and do not meet standard safety requirements and legal protection for consumers who use cosmetics which are produced without a production permit and do not meet standard safety requirements. This research uses normative legal research method. The results of the research show that the defendant in this case has fulfilled the elements for which a sentence can be carried out. The first element is an act carried out in accordance with Article 197 of Law of the Republic of Indonesia Number 36 of 2009 concerning Health, the second element violates Article 106 of Law of the Republic of Indonesia Number 7 of 2014 concerning Trade, and the third element violates Article 62 paragraph (1) Jo. Article 8 of Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection. Consumers experience losses as a result of using cosmetics that are produced without a production permit and do not meet standard safety requirements, so the defendant is required to compensate consumers for losses incurred in accordance with the provisions of Article 7 letter f with administrative sanctions in accordance with Article 60 Paragraph (2) Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection and criminal sanctions contained in Article 62 Paragraph (1) of Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection.